2016
DOI: 10.1039/c6tc00069j
|View full text |Cite
|
Sign up to set email alerts
|

Thermal stability and electrical conductivity of carbon-enriched silicon oxycarbide

Abstract: Silicon oxycarbide (SiOC) is an interesting polymer-derived system that can be tailored to embody many different properties such as lightweight, electrochemical activity, and high temperature stability. One intriguing property that has not been fully explored is the electrical conductivity for the carbon-rich SiOC compositions. In this study, a carbon-rich SiOC system is created based on the crosslinking and pyrolysis of polyhydromethylsiloxane (PHMS) and divinylbenzene (DVB) mixed precursors. The carbonrich n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
55
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 92 publications
(61 citation statements)
references
References 36 publications
3
55
0
Order By: Relevance
“…These outstanding properties are attributed to the unique microstructure of PDCs, composing of SiCN amorphous matrix and self‐assembled carbon cluster nanodomain (so called free carbon). Previous reports revealed that the concentration, conductivity, and structure of the free carbon are a key to affect the electric conductivity of PDCs . Chen and coworkers reported that the electric conductivity of SiBCN ceramics increased by five orders of magnitude when pyrolysis temperature increases from 1000°C to 1500°C and they stated that the remarkable increased electric conductivity is due to the increase in conductivity of free carbon phase by the amorphous carbon to nanocrystalline graphite transition of the free carbon .…”
Section: Introductionmentioning
confidence: 99%
“…These outstanding properties are attributed to the unique microstructure of PDCs, composing of SiCN amorphous matrix and self‐assembled carbon cluster nanodomain (so called free carbon). Previous reports revealed that the concentration, conductivity, and structure of the free carbon are a key to affect the electric conductivity of PDCs . Chen and coworkers reported that the electric conductivity of SiBCN ceramics increased by five orders of magnitude when pyrolysis temperature increases from 1000°C to 1500°C and they stated that the remarkable increased electric conductivity is due to the increase in conductivity of free carbon phase by the amorphous carbon to nanocrystalline graphite transition of the free carbon .…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Figure , the activation energies are fairly low; they also decrease with increasing Ni content, which proves that Ni‐activated graphitization results in the percolating conductive network to enable the electrical conductivity for the SiOC–Ni systems. In our previous study, the highest electrical conductivity values always occur at ~400°C due to the SiOC surface oxidation to SiO 2 before the sudden drop, as well as the break down of the conductive turbostratic carbon network under the electrical field. In this study, with the Ar atmosphere, the oxidation problem is not applicable and the electrical conductivity drops after 800‐900°C.…”
Section: Resultsmentioning
confidence: 79%
“…Our previous studies about pure SiOCs report that the SiOC matrix is composed of a homogeneous network of Si–O–C structures and free carbon at 800°C‐1100°C pyrolysis temperatures. The SiC x O y matrix is featureless in which the free carbon is dispersed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Upon further heating to temperatures above 1000°C, SiO 2 and free carbon phases form in the SiOC matrix; at temperatures above approximately 1300°C, the SiOC matrix further phase separates into additional SiO 2 and carbon, as well as SiC nanocrystals . The formation temperature and content of each of the phases can be controlled by tailoring the polymer precursors and pyrolysis conditions . However, the ceramic yield is generally ≤70% and severely limits the practical uses.…”
Section: Introductionmentioning
confidence: 99%